Caracterização do gene da proteína capsidial do Grapevine virus A em videiras afetadas pela acanaladura do lenho de Kober no Estado de São Paulo - Moreira, Andreia E. [UNESP]; Gaspar, José O. [UNESP]; Camargo, Luis E. A.; Kuniyuki, Hugo (Sociedade Brasileira de Fitopatologia, 2004)
O presente trabalho caracteriza o gene codificador da proteína capsidial do isolado do Grapevine virus A (GVA) encontrado no Estado de São Paulo (GVA-SP). RNA total foi extraído de folhas e pecíolos de plantas de videira (Vitis spp.) da variedade 'Kober 5BB' e submetido a RT-PCR usando oligonucleotídeos desenhados para amplificar um fragmento entre as posições 6409 e 7175 do RNA do GVA (GenBank, acesso X75433). Foi obtido um fragmento de tamanho esperado (767 nt) que inclui o gene da proteína capsidial, codificando 198 aminoácidos. A seqüência do GVA-SP apresentou similaridade de nucleotídeos e aminoácidos de, respectivamente, 86-92,3% e 94,5-98% com isolados do GVA da Europa, África e Japão (Acessos X75433, AF441234, AF007415, AB039841) e da região Sul do Brasil (Acesso AF494187), sendo, entretanto, mais similar aos isolados africano e italiano.

We report the characterization of the coat protein gene of a Brazilian isolate of Grapevine virus A (GVA-SP). Total RNA was extracted from leaves and petioles of GVA infected plants of the grape (Vitis spp.) variety 'Kober 5BB' and subjected to RT-PCR using primers designed to amplify a fragment between positions 6409 and 7175 of the GVA RNA (GenBank Accession X75433). A fragment of the expected size (767 nt) was obtained which included the coat protein gene coding for 198 amino acids. The GVA-SP sequence displayed nucleotide and amino acid similarity of, respectively, 86-92.3% and 94.5-98% with GVA isolates from Europe, Africa and Japan (Accessions X75433, AF441234, AF007415, AB039841) and Southern Brazil (Accession AF494187). The highest identity, however, was with the African and Italian isolates.
Characterization of the coat protein gene of Grapevine virus A from Kober stem grooving-affected grapevines in the State of São Paulo, Brazil
Keywords: GVA; Vitivirus; Vitis spp.; Kober stem grooving; complexo do lenho rugoso; seqüenciamento; Filogenia